2020
DOI: 10.1051/matecconf/202030802004
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Mode Choice at Sharjah University City, United Arab Emirates

Abstract: A growing interest in the behaviour of travelers to university campuses has recently emerged whether by university administrators or transport officials. Understanding the modal choice determinants of university travellers increases the opportunity for finding appropriate policies and solutions to reduce traffic congestion and parking needs as well as to encourage active transportation hence achieving more sustainable mobility. This research study investigates the differences in mode choice habits among the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
4
2
Order By: Relevance
“…Also, it is an indication that public transport holds great potentials in providing a sustainable transport system in the city. However, the outcome of this result differs from the existing studies (Al-Salh & Esztergas-Kiss, 2021; Drliciak et al, 2020; Guerra & Li, 2021; Novačko et al, 2020; Obaid & Hamad, 2020) found the USA,, Europe, and Middle east which indicate that private transport was the most preferred mode for intra urban trips.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Also, it is an indication that public transport holds great potentials in providing a sustainable transport system in the city. However, the outcome of this result differs from the existing studies (Al-Salh & Esztergas-Kiss, 2021; Drliciak et al, 2020; Guerra & Li, 2021; Novačko et al, 2020; Obaid & Hamad, 2020) found the USA,, Europe, and Middle east which indicate that private transport was the most preferred mode for intra urban trips.…”
Section: Discussioncontrasting
confidence: 88%
“…Moreover, Hu et al (2022) used nested logit model, a type of discrete choice models, to estimate commuter mode choice in dual-earner household in a small Chinese city. The outcome of this study is not completely consistent with the output from multinomial logit models (Drliciak et al, 2020; Novačko et al, 2020; Obaid & Hamad, 2020; Rasaizadi & Askari, 2020). The study found that the mode choice for female commuters consist of e-bike (63.4%), car (23.2%), walk (4.3%), shuttle bus (3.3%), transit bus (2.9%), motorcycle (1.5%), and bike (1.4%).…”
Section: Literature Reviewcontrasting
confidence: 62%
See 2 more Smart Citations
“…Obaid and Hamad, (2019), developed a multinomial logit model to predict the mode choice for the University City of Sharjah in the United Arab Emirates. The results of the research showed that travel time and trip maker characteristics are the most important factors that affect the choice (Obaid & Hamad, 2020). Jonii, (2015, tried to develop a model to understand the behavior of trip makers and try to convert them to public transportation using the logarithm model and SPSS statistical package.…”
Section: Introductionmentioning
confidence: 99%